Impact of Stock Market Liquidity on Investment of Listed Enterprises: Evidence from Vietnam - Tran, Ngoc Tho (University of Economics Ho Chi Minh City, 2023)
This paper studies the effects of market liquidity and other factors on investment of non-financial companies listed on Vietnam stock exchange for the 2008–2013 period by adopting different measures of investment and liquidity, and considering the impact of interaction between liquidity and others, including issuing, financial constraints, and growth opportunities, on firm investment. The estimated results of DGMM with fixed effects and interacting variables prove that stock market liquidity negatively relates to the investment. We do not find any compelling evidence of the liquidity–investment nexus among firms with tighter financial constraints and better investment opportunities. However, we do find the relations between firm investment and financial leverage and also firm investment and cash flows.